Postcard from Svante Arrhenius to Georg Bredig, June 1902 - Arrhenius, Svante (1902)
Postcard from Svante Arrhenius (1859-1927) to Georg Bredig (1868-1944) congratulating Bredig on the birth of his first born son, Max Albert Bredig (1902-1977). Arrhenius gives Bredig updates on his own travels and thanks him for his hospitality when he hosted two sisters, who are assistants to Arrhenius and Sven Otto Pettersson (1848-1941).
Keywords: Arrhenius, Svante, 1859-1927; Bredig, Georg, 1868-1944; Chemists; Nobel Prize winners